Impact of gastroplasty on salivary characteristics, dental health status and oral sensory aspects: A controlled clinical study. (10th July 2022) - Marquezin, Maria Carolina Salomé; Scudine, Kelly Guedes de Oliveira; Lamy, Elsa; Finassi, Carolina Martins; Carreira, Laura; Segura, Wilson Dias; Rasera, Irineu; Pessotti, Elisane Rossin; Castelo, Paula Midori
Abstract: Background: Saliva is a non‐invasive source of biomarkers useful in the study of different pathophysiological conditions. The qualitative and quantitative study of saliva, as well as the assessment of oral health, can be particularly useful for a better understanding of obesity due to its importance in the food oral perception and ingestion. Objectives: To evaluate the effect of treatment of morbid obesity (dietary counselling versus gastroplasty) on salivary characteristics, oral sensory perception and dental health in a controlled study. Methods: Seventy‐three adults (60 females; 19–59 years) with morbid obesity were divided in: Control group (CG; n = 34) followed‐up during a 6‐months dietary programme, and Gastroplasty group (GG; n = 39) evaluated immediately before, 3 and 6 months after gastroplasty. Dietary habits, Oral Health Impact Profile and xerostomia complaints were investigated by interview. The clinical examination included anthropometric and caries experience evaluation. Salivary flow rate, buffering capacity, total protein and alpha‐amylase levels, and sensitivity for the four basic tastes were assessed. Two‐way mixed model and sign test were applied. Results: Physical and clinical aspects did not differ between groups in the beginning of the study, and GG showed a rapid weight loss after surgery ( p < .001). An improvement in most of the dietary aspects was observed, especially in the GG. A worsening in the dental health status was observed over time in both groups, with an increase in the number of filled and decayed teeth. CG showed a better oral health‐related quality of life, while xerostomia complains increased in GG after gastroplasty. Salivary flow rate remained stable in both groups, but a decrease in buffering capacity, total protein and alpha‐amylase activity was observed in GG after 6‐months; taste sensitivity increased from baseline to 6‐months in GG ( p < .05). Conclusion: After 6‐months of follow‐up, patients undergoing gastroplasty presented an improvement in dietary habits and taste sensitivity. However, changes in saliva composition and a worsening in dental health status and xerostomia complaints were also observed. Abstract : After 6‐Months of follow‐up, patients undergoing gastroplasty presented an improvement in dietary habits and taste sensitivity. However, changes in saliva composition and a worsening in dental health status and xerostomia complaints were also observed.